Xylitol Improves Pancreatic Islets Morphology to Ameliorate Type 2 Diabetes in Rats: A Dose Response Study. Issue 7 (24th June 2014) - Rahman, Md. Atiar; Islam, Md. Shahdiul
Abstract Xylitol has been reported as a potential antidiabetic sweetener in a number of recent studies; however, the most effective dietary dose and organ‐specific effects are still unclear. Six‐week‐old male Sprague‐Dawley rats were randomly divided into 5 groups: normal control (NC), diabetic control (DBC), diabetic xylitol 2.5% (DXL2.5), diabetic xylitol 5.0% (DXL5), and diabetic xylitol 10.0% (DXL10). Diabetes was induced only in the animals in DBC and DXL groups and considered diabetic when their nonfasting blood glucose level was >300 mg/dL. The DXL groups were fed with 2.5%, 5.0%, and 10% xylitol solution, whereas the NC and DBC groups were supplied with normal drinking water. After 4‐wk intervention, body weight, food and fluid intake, blood glucose, serum fructosamine, liver glycogen, serum alanine transaminase, aspartate transaminase, lactate dehydrogenase, creatine kinase, uric acid, creatinine, and most serum lipids were significantly decreased, and serum insulin concentration, glucose tolerance ability, and pancreatic islets morphology were significantly improved in the DXL10 group compared to the DBC group. The data of this study suggest that 10% xylitol has the better antidiabetic effects compared to 2.5% and 5.0% and it can be used as an excellent antidiabetic sweetener and food supplement in antidiabetic foods.